The Influence of Digital Platforms, Organizational Readiness and Innovation Culture on the Performance of MSMEs in the Fisheries and Maritime Sector - Wahyuni, Ayu Endah; Prihardianto, Rahaditya Dimas (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
MSME (micro, small and medium enterprises) actors in the fisheries and marine sectors in Indonesia are faced with increasing global competition. Business actors must be able to increase their competence and capacity for empowering technology and innovation. However, limited knowledge of utilizing digital access is a major obstacle, especially for MSME actors in the fisheries and marine sectors. Apart from that, the ability of MSME players to innovate products is still limited. This is proven based on the research innovation index in Indonesia, which has experienced a decline in relation to human resources, research, infrastructure, market updates, and business. A fairly low indicator relates to innovation capacity, which has an impact on an increasingly declining innovation culture. This research aims to analyze the influence of digital platforms, organizational readiness, and innovation culture on the performance of MSMEs in the fisheries and marine sectors in the city of Surabaya. The unit of analysis for this research is 30 MSME actors in the city of Surabaya. This research produced five (five) research hypotheses, which were processed and analyzed using a partial least squares approach. The results of this research show that digital platforms have a significant effect on organizational readiness and innovation culture, as well as innovation performance. Likewise, organizational readiness has a significant influence on innovation performance. However, innovation culture does not show significance for innovation performance.